VL Gehun 953: A high yielding, rust-resistant, winter x spring wheat (Triticum aestivum L.) derivative, suitable for organic hills as well as inorganic Plains of Uttarakhand state of India - Kant, Lakshmi; Pant, Subodh kumar; Jain, Sanjay Kumar; Raghu, Borehalli Rangaswamy; Pandey, Bhawani Dutt; Shankar, Daya; Mahanta, Dibakar; Jethi, Renu; Pattanayak, Arunava; Bankoti, Gopal Singh; Malkani, Laxmi Dutt (Journal of Cereal Research, 2025)
VL Gehun 953- a high yielding variety was released by Uttarakhand seed Sub-Committee and notified by Central Sub-Committee on Crop Standards, Notification and Release of Variety for commercial cultivation under irrigated inorganic production conditions of Uttarakhand Plains and timely sown irrigated organic production situations of Uttarakhand hills. It recorded (3.34 tha-1) 7.46% higher grain yield compared to the best check VL Gehun 907 under irrigated organic conditions of Uttarakhand hills. Likewise, it produced (4.47 tha-1) 6.93% higher grain yield compared to the best check PBW 343 under irrigated situations of Uttarakhand Plains. It provided greater level of resistance to both stripe and leaf rust and recorded average coefficient of infection (ACI) of 0.27 for stripe rust and 2.0 for leaf rust under artificial inoculation situations, respectively. It contains 10.4 % average protein and 82.8 kghl-1 hectoliter weight, therefore, possessing good quality for chapatti making with good flour recovery. The large scale demonstrations conducted in different districts of Uttarakhand has proved its acceptability among the farmers. The spread of this variety in entire Uttarakhand state (Hills under organic and Plains under inorganic conditions) is anticipated to enhance wheat productivity of the state. In addition, it would also help in curtailing the rust inoculum both in hills as well as plains of Uttarakhand owing to its better resistance DOI.10.25174/2582-2675/2020/86682